Compostagem de resíduo sólido de abatedouro avícola - Sunada, Natalia da Silva [UNESP] (2015)
The great demand for animal protein was responsible for the increase on the broilers production and hence, the generation of waste from the poultry slaughter was increased as well, which in turn, propelled the development of techniques that allow the reuse and recycling of these wastes. The objective of this study was to evaluate the efficiency of composting on the treatment and recycling of solid waste from poultry slaughterhouse. The solid waste was from a commercial poultry slaughterhouse and was composed of viscera, muscle, fat, bone, blood and feathers that was mixed with a source of carbon, rice husk. Initially, a windrow with a volume of 1.5m(3) was built, and then some parameters were monitored: temperature, total solids (TS), volatile (VS), N, P, K, organic carbon (C), composting organic matter (COC), organic matter resistant to composting (MORC), chemical oxygen demand (COD), mass and volume of the windrow, most probable number (MPN) of total and fecal coliforms, as well as their reductions during the process. The maximum temperature reached in the center of the windrow was 53.3 degrees C (weekly average) since reductions of weight of TS and VS and volume during the pre-composting were 36.1, 44.3 and 23.3%, respectively and during the composting process was 21.8, 23.8 and 4.4%. The low volume reduction can be associated with high concentrations of MORC (40.1%) which can be mainly related to the quality of the carbon source. The process produced satisfactory total reductions of TS, VS and volume that were respectively, 50.1, 57.5 and 26.7%. However reductions were observed in 43% of amount of nitrogen in the final compound. Despite reductions in nitrogen content, composting proved to be an effective method in the treatment of solid waste from poultry slaughterhouse.